Risk Management Practices on the Financial Performance of Commercial Banks in Kenya - Ndung'u, Caroline (University of Embu, 2020)
In the world there are always signs of change which come up with various ways of doing business to achieve the outcomes, bankers are expected by their customers to provide them with loans and advances to make up any shortfall in their funds for transactional motive. Risk is inherent in every banking sector which is required to be managed by employing more competent staff. The core objective of this study was to analyze the risk management practices embraced by commercial banks in Kenya to enhance their profitability. The risk management practices included; risk monitoring, risk mitigation, adequate internal controls, risk measurement, capital adequacy, risk management environment and investment guidelines. Secondary data was obtained from CBK annual reports, the five years (2011-2015) annual ROE ratio was averaged to form dependent variable (financial performance) and regression model adopted to analyze the data. The study established that there is a positive relationship between financial risk management practices and financial performance of commercial banks with a better risk measurement procedures and techniques as well as tight internal controls performing better. It was concluded that risk management practices significantly affected the financial performance of commercial banks. The study recommends that a research should be done on challenges facing commercial banks in management of financial risk.